Application Of Digital Marketing Technologies In The Industry Of Uzbekistan: Current State And Development Trends - PhD, Associate Professor Matrizaeva Dilaram Yusupbaevna; PhD, Associate Professor Kutbitdinova Mokhigul Inoyatovna (Genius Journals, 2025)
This article analyzes the current state of the use of digital marketing technologies in industrial enterprises of Uzbekistan, as well as the prospects for their development. The study examines the impact of ongoing reforms based on the Strategy "Digital Uzbekistan - 2030" and other regulatory documents on industrial marketing. Both opportunities and barriers to the effective implementation of digital tools are identified. Based on the results of the survey, analysis of foreign experience (USA, Germany, Korea) and national practice, it is clarified how industrial entities use digital marketing tools. Particular attention is paid to current issues such as the lack of holistic marketing strategies, shortage of qualified specialists and weak IT infrastructure. In conclusion, regulatory, organizational, technological and scientific proposals for the development of this area are presented.
Keywords: Digital Marketing; Industrial Enterprises